Effect of different chewing gums on dental plaque pH, salivary pH, and buffering capacity in children: A randomized controlled trial - Kameshwaran Muralikrishnan; Sharath Asokan; P R Geetha Priya (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study is to evaluate and compare the changes in dental plaque pH, salivary pH, and its buffering capacity after the use of three different chewing gums for 1 month in children aged 8-12 years. Methods: This randomized controlled clinical trial consisted of 90 children with Decayed, missing, Filled teeth (dmft/DMFT) <3. They were randomly divided into three groups to receive one of the following interventions: (a) chewing gum containing xylitol, (b) chewing gum containing casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), and (c) chewing gum containing propolis. Oral prophylaxis was done, and saliva and plaque samples were collected after 48 h as preintervention data. Participants within the experimental groups chewed gums for 10 min, two times a day for a period of 1 month. Pre-and postintervention unstimulated saliva samples were analyzed to compare the changes in dental plaque pH, saliva pH, and buffer capacity. The data were then statistically analyzed using SPSS software. Paired t-test and Student's t-test were done for mean score analysis. Results: There was a statistically significant increase in plaque pH (P = 0.001) level in all three groups. Propolis chewing gum showed an increased salivary pH level (P = 0.036). When compared between genders, girls showed a significant increase in plaque pH level in all three groups and an increase in salivary pH level in xylitol group. Conclusion: Chewing gum containing xylitol can regulate the dental plaque pH, salivary pH, and buffer capacity in a significant way than CPP-ACP and propolis chewing gum.